3D graphene paper-based tandem metal-free thin-film supercapacitors with integrated 200 V output - Huilong Liu; Litian Gan; Renji Chen; Zhiwen Xiao; Yun Chen; Hongzuo Yang; Yahang Liu; Baisheng Wu; Ching-Ping Wong; Xin Chen (International Journal of Extreme Manufacturing)
The development of high-voltage tandem thin-film supercapacitors (TFSCs) has been limited by the issues such as expensive electrode materials, indispensable commercial separators and metal current collectors, and complex manufacturing processes. Herein, we develop a potentially scalable approach to address all these issues by using CO _2 laser pyrolysis of polyimide (PI) paper into the three-dimensional (3D) morphology of graphene paper in air. The formation process and mechanism of PI to graphene were clarified by microstructure and chemical characterizations and reaction molecular dynamics. The influences of laser scan density, power, defocus, and scan speed on the sheet resistance, longitudinal resistance, Raman spectra, and electrochemical performance of graphene papers were systematically investigated. Results indicate that high-quality graphene papers with ultralow sheet resistance (4.88 Ω·square ^−1 ) and longitudinal resistance (3.46 Ω) and extra-large crystalline size (96.1 nm) were achieved under optimized process parameters. The graphene papers can simultaneously serve as active electrode materials, current collectors, and interconnectors. The active area of electrodes is defined by a PI mask, with the help of which a hydrogel electrolyte functions as a separator. The assembled graphene paper-based TFSCs demonstrate outstanding electrochemical performance and mechanical flexibility, with the areal capacitance of 54.5 mF·cm ^−2 , energy density of 10.9 μWh·cm ^−2 , and cycle stability retention of 86.9% over 15 000 cycles. Moreover, all the tandem metal-free TFSCs, ranging from 1 to 160 cells, show excellent performance uniformity. The output voltage increases linearly from 1.2 V to 200 V. Significantly, the 160-tandem TFSCs exhibit a high voltage density within a compact volume of ∼3.8 cm ^3 . This work provides an avenue for achieving tandem metal-free TFSCs in a simple and efficient manner.